A Randomized Comparison of the Effects of Continuous Thoracic Epidural Analgesia and Intravenous Patient-Controlled Analgesia After Posterior Spinal Fusion in Adolescents. Issue 3 (1st May 2000) - Cassady, Joseph F.; Lederhaas, George; Cancel, Dawn D.; Cummings, R. Jay; Loveless, Eric A.
Abstract : Background and Objectives: Pain and gastrointestinal dysfunction are primary factors that delay recovery after posterior spinal fusion. Previous reports suggest that the choice of analgesic management may effect the course of recovery. This prospective, randomized study compared continuous thoracic epidural analgesia and patientcontrolled analgesia in the postoperative care of adolescents undergoing posterior spinal fusion for idiopathic scoliosis. Methods: Patients between 11 and 18 years of age were randomized to receive continuous thoracic epidural analgesia with bupivacaine-fentanyl (CEA, n = 17) or intravenous patient-controlled analgesia with morphine sulfate (n = 16). After surgery under general anesthesia, pain intensity was evaluated using a self-report visual analog scale (VAS). Postoperative time to resumption of bowel sounds, liquid intake, and side effects were also recorded. Results: There were no significant differences between groups in VAS pain scores, side effects, or time to resumption of liquid intake. There was a significant difference ( P = .0089) between groups in return of bowel sounds, which occurred earlier in patients receiving CEA. Conclusions: Continuous epidural analgesia and patient-controlled analgesia are comparably effective and safe after posterior spinal fusion. Return of bowel sounds occurred significantly more rapidly in patients receiving CEA postoperatively.